2021
DOI: 10.1002/anie.202014323
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pyridinic Nitrogen in the Mechanism of the Oxygen Reduction Reaction on Carbon Electrocatalysts

Abstract: The introduction of pyridinic nitrogen (pyri-N) into carbon-based electrocatalysts for the oxygen reduction reaction is considered to create new active sites. Herein, the role of pyri-N in such catalysts was investigated from a mechanistic viewpoint using carbon black (CB)-supported pyri-N-containing molecules as model catalysts; the highest activity was observed for 1,10-phenanthroline/CB. X-ray photoemission spectroscopy showed that in acidic electrolytes, both pyri-N atoms of 1,10-phenanthroline could be pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 18 publications
0
42
0
Order By: Relevance
“…Prof. Nakamura and Prof. Ozaki also investigated ORR in nitrogen-doped carbon materials for fuel cell applications. [240][241][242][243] Using STM, Zhao et al 244 reported images of individual nitrogen atoms doped in monolayer graphene. Measurements using X-ray photoelectron spectroscopy and near-edge X-ray absorption ne structure spectroscopy conrmed the presence of N dopants in graphene lattices as well as the formation of in-plane N-C bonds, indicating that the nitrogen atoms were substituted into the graphitic matrix.…”
Section: Substitutional Impurity Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prof. Nakamura and Prof. Ozaki also investigated ORR in nitrogen-doped carbon materials for fuel cell applications. [240][241][242][243] Using STM, Zhao et al 244 reported images of individual nitrogen atoms doped in monolayer graphene. Measurements using X-ray photoelectron spectroscopy and near-edge X-ray absorption ne structure spectroscopy conrmed the presence of N dopants in graphene lattices as well as the formation of in-plane N-C bonds, indicating that the nitrogen atoms were substituted into the graphitic matrix.…”
Section: Substitutional Impurity Defectsmentioning
confidence: 99%
“…280 Substitutional nitrogen doping has been done via CVD or electrochemical treatment. [281][282][283] The effect of nitrogen doping on the electronic properties of pristine or point-defected graphene has been widely studied from both the experimental and computational sides [241,[311][312][313]. 221,[283][284][285][286] However, few studies have addressed doping in extended line defects.…”
Section: One-and Two-dimensional Defects (Topological Defects)mentioning
confidence: 99%
“…And then, we calculated turnover frequency (TOF) to explore the intrinsic ORR activity of our designed catalysts. As revealed by Figure S17 in the Supporting Information, the TOF of active site (carbon atoms connected to pyridinic nitrogen [78,79] ) within DC/NTi 3 C 2 is defined to be 0.43 e s −1 per site, obviously higher than that of DC/Ti 3 C 2 (0.33 e s −1 per site), DC/Ti 3 C 2 200 (0.36 e s −1 per site), DC/Ti 3 C 2 400 (0.29 e s −1 per site). Additionally, the resist ance to methanol crossover and longterm catalytic durability are deemed as essential properties for the ORR electrocatalyst in the practical application.…”
Section: Resultsmentioning
confidence: 99%
“…[ 30 ] These various N species contribute to different chemical and electronic environments for adjacent C atoms, thus leading to different electrocatalytic activities, in which pyridinic N and graphitic N are commonly considered to be favorable for enhancing electrocatalytic activities. [ 31 ] DAP‐HPNC‐1020 has more pyridinic N and graphitic N than oPD‐HPNC‐1020 and mPD‐HPNC‐1020, which might pave the way for its better electrocatalytic activities. In addition, it can be concluded that pyridinic N, pyrrolic N, and oxidized N all underwent conversion to graphitic N with increasing temperature (Figure S7, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%